Manajemen Pembelajaran Dalam Meningkatkan Perkembangan Kognitif Anak Usia Dini - Halawa, Solingkari; Sni, Seoni; Zendato, Petrus Damai; Tanasyah, Yusak (Indonesian Journal of Religious, 2022)
Learning management is an important thing in the process of teaching and learning activities, learning management influences student achievement in academic and non-academic activities. The purpose of this study is based on learning management to improve early childhood cognitive abilities by using the storytelling method and the question-and-answer method. This type of research is the bibliography, the data collected in this study are two types of data, namely primary data, and secondary data. Data obtained from library research (library). The data collection technique used by this researcher is a literature study. The data analysis technique in this study used qualitative analysis techniques in a deductive way. The research results obtained that the storytelling method and the questioning method play an important role in improving the cognitive development of early childhood which can make it easier for children to carry out teaching and learning activities.    Manajemen pembelajaran merupakan hal penting dalam proses kegiatan belajar mengajar, manajemen pembelajaran berpengaruh terhadap prestasi peserta didik dalam kegiatan Akademik dan non akademik. Tujuan penelitian ini Berdasarkan manajemen pembelajaran untuk meningkatkan kemampuan kognitif anak usia dini dengan menggunakan metode bercerita dan metode Tanya jawab, Jenis penelitian ini adalah bibliografi, data yang dikumpulkan dalam studi ini adalah dua jenis data yaitu data primer dan data sekunder. Data diperoleh dari riset kepustakaan (library). Teknik pengumpulan data yang digunakan peneliti ini adalah studi kepustakaan. Teknik analisis data pada penelitian ini dengan menggunakan teknik analisa kualitatif dengan cara deduktif. Hasil penelitian yang diperoleh bahwa metode bercerita dan metode bertanya sangat berperan penting dalam meningkatkan perkembangan kognitif anak usia dini dapat memudahkan anak dalam melakukan kegiatan belajar mengajar.